Rehabilitation of Internally Displaced Persons and the Support of Nepal Peace Trust Fund in Gorkha District - Gurung, Shibaji (Journal of Political Science, 2022)
Rehabilitation of Internally Displaced Persons (IDPs) is an important agenda in the peace process of Nepal. The Ministry of Peace and Reconstruction and particularly, the Nepal Peace Trust Fund (NPTF) supported the rehabilitation process of these IDPs who were displaced during the Maoist insurgency. This paper has tried to analyze the process of rehabilitation of IDPs and the challenges faced during the process. It has also tried to assess the support of NPTF in the rehabilitation of IDPs. The research was carried out in the Gorkha district. It has applied a qualitative method during the process of research. The interview was used as the primary tool for collecting data. The IDPs registered at the District Administration Office (DAO) were purposively selected and interviewed till the theoretical saturation. The IDPs returned to their place of origin after the signing of CPA in 2006. But they faced a lot of challenges in the rehabilitation process, such as the condition of insecurity, difficulty in reestablishing secured livelihood conditions, psychological effects, lack of proper housing and lack of an appropriate local mechanism to facilitate the rehabilitation process. Most of the IDPs have received the relief package of Rs. 7200 through DAO provided by NPTF. This is the very minimum amount; and the IDPs used it as a household expense rather than using it in the rehabilitation process. So, the NPTF’s relief package did not have a significant contribution to the rehabilitation of IDPs.